Pacific finance sector brief Palau. (Pacific finance sector briefs., 2019)
Palau has one of the most monetized economies in the Pacific, but credit growth is sluggish due to legal prohibitions and structural deficits. The countrys financial system is reasonably diverse with five commercial banks operating, three of which are foreig owned. It also has its own development bank, the National Development Bank of Palau, as well as access to services of the Pacific Islands Development Bank. Palau has a social security retirement fund and an insurance corporation. A priority for the finance sector is to reduce the structural and legal impediments that restrict commercial bank lending.